Uji daya hambat anti jamur ekstrak minyak atsiri Cinnamomun burmanii terhadap pertumbuhan Candida albicans - Ali Yusran (Journal of Dentomaxillofacial Science, 2009)
Many kinds of spicy plants grow in Indonesia. One of them is kayu manis(Cinnamomun burmanii) which is used not only for cooking, but also as traditionalmedicine. One of the components contained in the bark and leaves of kayu manis isvolatile oil. Generally, volatile oil has an antifungal effect, therefore it’s inhibitoryeffect was tested against fungi. The study was conducted to evaluate the anti fungaleffect of kayu manis to Candida albicans. The method used in this study wasdetermination of minimum inhibitory concentration (MIC)followed by determinationof zone inhibition around the disc. The result showed that kayu manis has the highestantifungal activity against Candida albicans with 1% of MIC.